#TITLE_ALTERNATIVE# - AYUNINGTYAS (NIM 10104055), ASTRID
Portofolio selection in finance using classic or traditional methodology has produced a portofolio with unstable characteristic such that it is not meet with the investor's expectation. This phenomenon is due to the fact that the financial datas are not distribute normally and the estimated parameters used to select the portofolio disturbed by the data's outliers. In this thesis, the portofolio were selected using the certain method that capable to detect the outliers on the financial data. This method is known as Minimum Covariance Determinant (MCD) which produce a robust estimator enable to estimate mean and covariance parameters by minimizing its covariant determinant. After both parameters became robust then the optimal proportion of the portofolio could be found using the Mean-Variance model of Markowitz.